Reduction of circulating FABP4 level by treatment with omega-3 fatty acid ethyl esters. Issue 1 (December 2016) - Furuhashi, Masato; Hiramitsu, Shinya; Mita, Tomohiro; Omori, Akina; Fuseya, Takahiro; Ishimura, Shutaro; Watanabe, Yuki; Hoshina, Kyoko; Matsumoto, Megumi; Tanaka, Marenao; Moniwa, Norihito; Yoshida, Hideaki; et al.
Abstract Background Fatty acid-binding protein 4 (FABP4/A-FABP/aP2) mainly expressed in adipocytes is secreted and acts as an adipokine. Increased circulating FABP4 level is associated with obesity, insulin resistance and atherosclerosis. However, little is known about the modulation of serum FABP4 level by drugs including anti-dyslipidemic agents. Methods Patients with dyslipidemia were treated with omega-3 fatty acid ethyl esters (4 g/day;n = 14) containing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) for 4 weeks. Serum FABP4 level was measured before and after treatment. Expression and secretion of FABP4 were also examined in mouse 3T3-L1 adipocytes treated with EPA or DHA. Results Treatment with omega-3 fatty acid ethyl esters significantly decreased triglycerides and serum FABP4 level (13.5 ± 1.5 vs. 11.5 ± 1.1 ng/ml, P = 0.017). Change in FABP4 level by omega-3 fatty acids was negatively correlated with change in levels of EPA + DHA (r = −0.643, P = 0.013), EPA (r = −0.540, P = 0.046) and DHA (r = −0.650, P = 0.011) but not change in the level of triglycerides or other fatty acid composition. Treatment of 3T3-L1 adipocytes with EPA or DHA had no effect on short-term (2 h) secretion of FABP4. However, gene expression and long-term (24 h) secretion of FABP4 were significantly reduced by treatment with EPA or DHA. Conclusions Omega-3 fatty acids decrease circulating FABP4 level, possibly by reducing expression and consecutive secretion of FABP4 in adipocytes. Reducing FABP4 level might be involved in suppression of cardiovascular events by omega-3 fatty acids.